Multi criteria decision making on load shedding scheme in an islanded system - Jakuil, Alester G (2013)
Any interruptions to the electrical system can cause loss of the power supply due to the burden of the generator. In industries, intenuption in power system can cause million of losses when the shortage of supply occurs. The supply will be back-upped in the storage system. However, if the over demand is uncontrolled, or when there is no decision-making in removing a certain load, there will be a trouble in the power system. The decision should involve removing certain loads depending on some importance or criteria. This requires some decision-making in order to choose the best load(s) to be cut off. In order to do so, Multi Criteria Decision Making (MCDM) can be applied to determine the load shedding scheme in the power system. The objective of this thesis is to justify a load shedding scheme for an islanded power system. This project proposes methodologies for load shedding scheme for the islanded electric power system by using Analytic Hierarchy Process (AHP), Fuzzy Analytic Hierarchy Process (Fuzzy AHP) and Technique for Order Preference by Similarity to Ideal Solution (TOPSIS). In this project, the load shedding scheme is applied to islanded Microgrid Ranau power system. From this project, a series of analyses are conducted and the results are determined. Analyses are made, and the results have shown that AHP, Fuzzy AHP and TOPSIS to determine the load shedding scheme for Ranau Microgrid system. Among these three MCDM methods, the result shown by TOPSIS is the most effective solution because of the effectiveness of load shedding is the highest.